Paired whole exome and transcriptome analyses for the Immunogenomic changes during concurrent chemoradiotherapy in esophageal squamous cell carcinoma. Issue 1 (16th May 2019) - Park, Sehhoon; Joung, Je-Gun; Min, Yang Won; Nam, Jae-Yong; Ryu, Daeun; Oh, Dongryul; Park, Woong-Yang; Lee, Se-Hoon; Choi, Yoon La; Ahn, Jin Seok; Ahn, Myung-Ju; Park, Keunchil; et al.
Abstract : Background: The immunogenomic changes triggered by concurrent chemoradiation therapy (CCRT), a standard neoadjuvant treatment for locally advanced esophageal squamous cell carcinoma (ESCC), are unknown. We aimed to analyze the early immunogenomic changes in ESCC induced by CCRT and to correlate them with clinical outcomes. Methods: We collected biopsy samples from 40 patients with ESCC and the surgical candidates were treated with 5-fluorouracil (5-FU)/Cisplatin and concurrent radiation therapy. Endoscopic biopsy was performed before and after one treatment cycle of 5-FU/Cisplatin and 5 to 18 fractions of radiation. We analyzed immunogenomic changes using paired whole-exome sequencing ( n  = 29) and paired whole-transcriptome sequencing (WTS, n  = 23). Multiplex immunohistochemistry (IHC) was conducted in four representative pair samples. Results: Fourteen out of 23 WTS samples (60.8%) showed increased immune scores after CCRT, as calculated by ESTIMATE. The rate of progression-free survival was higher in patients with increased immune scores compared with the remaining patients (83.1% vs. 57.1%, p  = 0.25). Tumor mutation burden and neoantigen load were significantly reduced after CCRT ( p  < 0.001). We observed no specific correlation with non-synonymous mutations and no changes in the single-nucleotide variant spectrum after CCRT. Post-CCRT samples were enriched in gene sets related to immune signaling pathways, such as interferon gamma signaling and CD28 co-stimulation. Multiplex IHC showed an incremental trend in the proportion of CD4 positive cells in cytokeratin positive region after CCRT. However, CD8, CD20, FOXP1, PD-L1 showed no definitive trend. Proportion of immune cells calculated by CIBERSORT, showed that significant increase in neutrophils after CCRT. Conclusions: We have comprehensively analyzed the early immunogenomic changes induced in ESCC by CCRT and correlated them with clinical outcomes. Our results provide a potential basis for combining immunotherapy with CCRT for the treatment of ESCC.